জনস্বার্থে মামলা - Āina Sāliśa Kendra (Dhaka, Bangladesh) (ঢাকা : আইন ও সালিশ কেন্দ্র (আসক), 2003)
Contributed articles on the status of public interest litigation in Bangladesh and the activities of the associations involved with it.
Includes bibliographical references.
In Bengali.
Keywords: Citizen suits (Civil procedure) -- Bangladesh; Pressure groups -- Bangladesh